Social inclusion or exclusion? never-married singles in West Amman - Sabbah, Dana Mustafa (AUC Knowledge Fountain, 2010)
Due to the continuous belief in the centrality of marriage and family value in Arab countries, the noticeable increase in the average age of females' marriages in Jordan for the last years is starting to ring alarming bells. This is associated with the increasing numbers of the NMW and delayed marriages (in 2007 more than 100000 women over the age of 30 years were reported by Aljazeera as still not married, Aljazeera News 26 Dec, 2008). This is compounded by a delay in the average age of marriage for females, which rose from 21 years in 1979 to 27 years in 2002 (Department of Statistics-Jordan 2003). Using the lens of social exclusion, my paper investigates the lives of NMW whose ages ranged between 30- 49; I ask how do never married women navigate social spaces, how do they define and claim rights in their daily interactions, and what challenges and opportunities do they face? Particularly, I explore whether NMW are included or excluded from the different social settings in West Amman, and examine the meanings, forms and tactics they deploy in dealing with their inclusion/exclusion. In my research I focus on middle to upper middle class women, who are characterized by a mix of conservatism and liberalism. I conducted in-depth interviews with eleven NMW and a couple of NMM to unpack possible gender differences. My paper relays aspects of women's lived reality and describes the freedoms and restrictions experienced by single women living in urban spaces as factors shaping their wellbeing. I argue that changes in marriage and nuclear family constitute a vital part of gendered relations and wellbeing.